2010
DOI: 10.1007/s11256-010-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a “Model Minority”: Acquisition, Construction and Enactment of American Identity for Korean Immigrant Students

Abstract: While the ''model minority'' stereotype of Asian Americans and its negative effects has been documented elsewhere, relatively little attention has been paid to how recent Asian immigrant students begin to embrace the stereotype while in schools. This study explores the identity formation process for a group of recent Korean immigrant students as ''model minority'' in an urban high school to empirically document the process. Through interviews and observations, I learned that the immigrants acquired an unauthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This may be attributed to the 'model minority' nature of Koreans and how this factor plays into participation in the public sphere. They have been known to be a reserved, model minority group that did not speak up as much toward social issues, and that has to do with certain traits of the group as a whole (Lee & Park, 2008;Park, 2010). As a result, readers from this group may have chosen not to cause controversy by participating in the discussion forum with one's own ideas.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the 'model minority' nature of Koreans and how this factor plays into participation in the public sphere. They have been known to be a reserved, model minority group that did not speak up as much toward social issues, and that has to do with certain traits of the group as a whole (Lee & Park, 2008;Park, 2010). As a result, readers from this group may have chosen not to cause controversy by participating in the discussion forum with one's own ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many White Americans thought that AAPI cultures held values and traditions such as parental respect and authority, industriousness, obedience, and willingness to learn, which were perceived to directly affect their high educational achievement and professional occupations (Lew, 2004;Li, 2005;Suzuki, 2002). Some scholars noted that the "model minority" stereotype unofficially demonstrated that Asian Americans had finally been accepted by White middle-class society as a result of their hard work (Pang & Cheng, 1998;Park, 2011;Suzuki, 2002). Yet, the "model minority" stereotypical perception disguises the reality that AAPIs in America are not accepted in many sectors of society even compared to other minority groups (Hartlep, 2013;Nguyen, 2014;Pang, Han, & Pang, 2011;Sue & Okazaki, 1990).…”
Section: The Beginning Of the Model Minority Mythmentioning
confidence: 99%
“…The most attention to address the research questions is paid to the data from the interview. Based on the previous research on ESL parents' attitudes to the children's second language learning, the interview questions are structured (Chung, 2008;Kim, 2006;Park, 2011;Zhang & Slaughter-Defoe, 2009). The interviews were conducted in Korean, which both parents were comfortable to speak; the interviews were audio-recorded and transcribed.…”
Section: Data Collectionmentioning
confidence: 99%
“…The 'bullying' issue seems to be worth considering among adolescents, rather than college level students, because of their immature attitudes. 'Wangtta' is a phenomenon that refers to a certain majority of students excluding the minority students in the school (G. C. Park, 2011). There may be a numerous factors, such as socioeconomic gaps, personalities, and differences in speech or even appearance.…”
Section: Variety Of Mixed-codesmentioning
confidence: 99%